Finite element simulation of dislocation based plasticity and diffusion in multiphase materials at high temperature - Albiez, Jürgen (Schriftenreihe Kontinuumsmechanik im Maschinenbau / Karlsruher Institut für Technologie, Institut für Technische Mechanik - Bereich Kontinuumsmechanik, 2019)
A single-crystal plasticity model as well as a gradient crystal plasticity model are used to describe the creep behavior of directionally solidi?ed NiAl based eutectic alloys. To consider the transition from theoretical to bulk strength, a hardening model was introduced to describe the strength of the reinforcing phases. Moreover, to account for microstructural changes due to material ?ux, a coupled diffusional-mechanical simulation model was introduced.